Modelling of air boundary layer around the grinding wheel. (3rd March 2020) - Majumdar, Sujit; Mandal, Sudip; Biswas, Ishindra; Roy, Debasish; Chakraborty, Samik
ABSTRACT: This paper establishes the models of rotating air layer to predict the pressure of the air around the solid and grinding wheel of different dimensions and rotating at different speeds and finds the factors affecting the flow. Initially, a theoretical model has been developed from the Navier–Stokes (N–S) equation and compared with the experimental values at each stage. Results show that the effects of two proposed novel effect, namely 'compensating air' for the solid wheel and 'Majumdar-air' for the grinding wheel, along with the effect of surface and centrifugal force are responsible for the additional growth of air. The effects of 'compensating air' and 'Majumdar-air' near the wheel surface have been found to be 33% and 66% of the total pressure for the solid and grinding wheel of the same dimension, respectively, rotating at 2880 rpm. These two effects are responsible for a significant deviation of the experimental data from the theoretical model. Further, the theoretical model has been modified by introducing a correction factor in the equation. Flower Pollination Algorithm (FPA) has been used to optimize the parametric values of the modified model with a minimal error. The output of the modified model has been found consistent with the experimental result.